2004
DOI: 10.1089/ars.2004.6.914
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxidative Stress in Ischemia–Reperfusion-Induced Changes in Na+,K+-ATPase Isoform Expression in Rat Heart

Abstract: The aim of this study was to assess whether depression of cardiac Na+,K(+)-ATPase activity during ischemia/reperfusion (I/R) is associated with alterations in Na+,K(+)-ATPase isoforms, and if oxidative stress participates in these I/R-induced changes. Na+,K(+)-ATPase alpha1, alpha2, alpha3, beta1, beta2, and beta3 isoform contents were measured in isolated rat hearts subjected to I/R (30 min of global ischemia followed by 60 min of reperfusion) in the presence or absence of superoxide dismutase plus catalase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
34
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 32 publications
8
34
0
1
Order By: Relevance
“…Taken together, our results strongly support the suggestion that antioxidant enzymes are involved in the cardioprotection of CIHH against I/R insult. These results are consistent with previous findings showing that administration or overexpression of antioxidant enzymes can improve the recovery of the heart contractile function from I/R injury [30][31][32] , indicating that CAT has an important role in cardiac protection against I/R insult even though the its activity in the myocardium is low [33] . Some studies [16,17,34] , however, suggest a close correlation between the increase in antioxidant enzyme activity and the cardioprotection induced by various ischemic and non-ischemic preconditioning methods.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Taken together, our results strongly support the suggestion that antioxidant enzymes are involved in the cardioprotection of CIHH against I/R insult. These results are consistent with previous findings showing that administration or overexpression of antioxidant enzymes can improve the recovery of the heart contractile function from I/R injury [30][31][32] , indicating that CAT has an important role in cardiac protection against I/R insult even though the its activity in the myocardium is low [33] . Some studies [16,17,34] , however, suggest a close correlation between the increase in antioxidant enzyme activity and the cardioprotection induced by various ischemic and non-ischemic preconditioning methods.…”
Section: Discussionsupporting
confidence: 93%
“…Hearts in the CON+antioxidant enzyme (CON+SOD+CAT) group were perfused with an antioxidant mixture containing SOD (100 U/mL) [23] and CAT (120 U/mL) [23] for 10 min before ischemia until the end of I/R. To examine whether the beneficial effects of CIHH on I/R injury are a result of its increased antioxidant activity, 35 hearts (n=7 in each group) were subjected to a protocol of 20 min baseline perfusion and 30 min H 2 O 2 (300 μmol/L, a potent oxidant) [32] perfusion. Hearts in CON+antioxidant enzyme (CON+CAT) group were perfused with CAT (120 U/mL) for 10 min before H 2 O 2 treatment until the end of the protocol.…”
Section: Experimental Protocol and Groupsmentioning
confidence: 99%
“…While small amounts of ROS are required to activate osmoregulatory pathways (Wagner et al, 2013), larger and uncontrolled quantities lead to the degeneration or inactivation of the membrane-bound iontransporting pumps such as NKA (Kim and Akera, 1987;Kukreja et al, 1990), thus reducing osmoregulatory capacities. Invertebrates have rarely been the subject of this type of study, but many works using different mammalian cells show how pro-oxidant conditions not only induce lipid peroxidation, but also lead to a decrease in the activity of NKA (Dobrota et al, 1999;Ostadal et al, 2004;Thomas and Reed, 1990) or Ca 2+ -ATPase (Kaneko et al, 1989;Lee and Okabe, 1995), both of which are essential for osmoregulation in marine invertebrates.…”
Section: Redox Metabolismmentioning
confidence: 99%
“…Recent studies have indicated that changes in sarcolemmal and sarcoplasmic reticular membranes lead to the development of Ca 2ϩ -handling abnormalities and intracellular Ca 2ϩ overload due to the occurrence of oxidative stress in the I/R hearts (15,25,29,36,37,42,48). On the other hand, only scattered and conflicting information regarding the status of mitochondrial function with respect to their respiratory and oxidative phosphorylation activities in the I/R hearts is available in the literature (3,19).…”
mentioning
confidence: 99%